Return to Active Duty Lifestyle After Modified Brostrom. Issue 1 (19th August 2016) - Melton, Thomas J.; Dannenbaum, Joseph H.; Ryan, Paul M.; Robbins, Justin
Category: Ankle Introduction/Purpose: Ankle sprains are a common sports related injury and typically treated conservatively. Chronic ankle instability, however, may require surgical management when non-operative measures fail. The Brostrom procedure with Gould modification is the most frequently employed operation for chronic ankle instability with a record of good to excellent treatment outcomes. The purpose of our study was to evaluate the clinical outcomes of this procedure in an active duty population. Methods: A retrospective review of our electronic surgery records for a cohort of active duty patients aged 18-45 who were indicated for operative treatment of chronic ankle instability and who underwent surgical repair consisting of a standard Brostrom procedure with Gould modification at Madigan Army Medical Center between January 1, 2010 through April 30, 2014 was performed. All patients were treated by a single surgeon and had a minimum of one year follow-up. The electronic medical record was reviewed for each patient to determine their ability to remain on active duty status as well as their permanent lower extremity activity restrictions. Results: 127 total patients who met the inclusion criteria underwent Brostrom procedures with Gould modification during the study period. 23 out of 127 (18.1%) underwent Medical Evaluation Board (MEB) and separation from active duty for reasons related to their ankle. Another 11 patients underwent military separation for reasons unrelated to their ankle. 67 patients (52.7%) currently have permanent lower extremity profiles in the electronic record. 38 patients with permanent profiles have been able to meet retention standards and remain on active duty status. Of the 93 patients who were able to remain on active duty status, only 2 individuals changed their military occupational specialty (MOS). The remainder of patients remain on active duty status in their current MOS, completed their active duty obligation or reached planned retirement. Conclusion: Chronic ankle instability in active duty service members can be severely limiting. Brostrom procedure with Gould modification can provide significant improvement in symptoms and allow patients to remain on active duty status. However, in our high demand population approximately 50% of patients required some form of permanent activity restriction with nearly 20% requiring military separation. This is important information when counseling an active patient population about the expectations from surgical intervention for chronic ankle instability.